Low serum uric acid levels and levodopa-induced dyskinesia in Parkinson's disease - Soares, Nayron Medeiros; Pereira, Gabriela Magalhães; Dutra, Ana Carolina Leonardi; Artigas, Nathalie Ribeiro; Krimberg, Júlia Schneider; Monticelli, Bruno Elkfury; Schumacher-Schuh, Artur Francisco; Almeida, Rosa Maria Martins de; Rieder, Carlos Roberto de Mello (Arquivos de Neuro-Psiquiatria, 2023)
Background Levodopa is the most used and effective medication for motor symptoms of Parkinson disease (PD), its long-term use is associated with the appearance of levodopa-induced dyskinesia (LID). Uric acid (UA) is believed to play an important neuroprotective role in PD.Objective To investigate if serum UA levels are related with the presence of LIDs in PD patients. Also, we investigated the associations among UA levels and clinical features of PD.Methods We enrolled 81 PD patients (dyskinesia = 48; no dyskinesia = 33) in the present study. A blood sample was collected to evaluate serum UA levels, clinical evaluation included the following instruments: Montreal Cognitive Assessment (MoCA), Beck Depression Inventory II (BDI-II), MDS-Unified Parkinson's Disease Rating Scale (MDS-UPDRS), Hoehn and Yahr (HY), and the sub-item 4.1 of MDS-UPDRS IV (score ≥ 1). Additional relevant clinical information was obtained by a clinical questionnaire.Results Serum UA levels were lower in the dyskinesia group when compared with the no dyskinesia group. The same result was found in the UA levels of both men and women. The multivariate analysis showed lower uric acid levels were significantly associated with having dyskinesia (odds ratio [OR] = 0.424; 95% confidence interval [CI]: 0.221–0.746; p = 0.005). Additional analysis verified that serum UA levels are inversely correlated with depressive symptoms, disease duration, MDS-UPDRS IV and time spent with dyskinesia. A positive correlation was found with age at onset of PD symptoms.Conclusions The present study provides a possible role of serum UA levels in LID present in PD patients.
Keywords: Parkinson Disease; Uric Acid; Dyskinesias; Levodopa